PKM SMP MUHAMMADIYAH PADANG DALAM PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL PADA KETERAMPILAN MENULIS TEKS EKSPOSISI BERBASIS DIGITAL - Ria Satini; Rina Sartika (Kilau Publishing, 2023)
Expository text is a form of text or writing that contains information and knowledge. In general, expository text itself has the aim of providing an explanation or description of ideas, main ideas, opinions, information, and knowledge to the reader without intending to influence. To support the creation of teacher professionalism in creating effective learning, a Community Partnership Program (PKM) was held. PKM is carried out by guiding and providing training to students at SMP Muhammadiyah Padang, so they can use various learning media. The use of this learning media can help students to be more enthusiastic in the learning process on exposition text material. As a new, innovative learning media, the use of this learning media is the main attraction for students. Students no longer get material about exposition texts with lengthy theoretical presentations, but teachers directly provide learning with interesting learning media, one of which is digital-based audio-visual learning media. Keywords: learning media, audio visual, exposition text